Simulation of hydraulic power matching–based risk and economic evaluation among cascade hydropower stations in spot transactions - Zhang, Shuai; Ma, Guang-Wen; Huang, Wei-Bin; Tao, Chun-Hua; Yang, Bing-Quan; Xue, Yu-Lin (Frontiers in Energy Research, 2022)
The electricity market is evolving rapidly, from pre-bid to spot markets, where the transactions between producers and consumers have become crucial and are vulnerable to safety risks. In addition, the new modes of transaction are also becoming popular and are said to have some risks. To reveal the impact of the new electricity transaction mode - spot market, on the safety risk and generation benefit, this paper presents a simulation method connecting the transaction results and operation process. To verify the effectiveness of the proposed method, an actual cascade hydropower station (CHSs) in the Dadu river basin, Southwestern China, which comprises eight hydropower stations, is selected. Hydraulic power matching among CHSs is discriminated from four aspects with multiple indicators combined with the reality of a hydropower-dominated market in Sichuan, China. The dispatching decision-making process of hydropower generators is described with a multi-objective optimization model and then solved with a fast search strategy based on the classical output calculation method in hydrology. The security risks and economic damage hidden in the day-ahead market on a certain day are discovered and analyzed. The technology proposed provided support for bidding decisions in spot transactions and satisfied the reality during the transition period of electricity reform.